2019
DOI: 10.1007/s40430-019-2137-5
|View full text |Cite
|
Sign up to set email alerts
|

On the wake interference effects for flow around tandem bodies

Abstract: The present study investigates the wake interference effects for flow around two tandem cylinders under the effect of gap spacing ranging from 0.5 to 10. The flow Reynolds number is fixed at 150, and lattice Boltzmann method is used as a numerical tool for this study. The results show that three different regimes exist depending on gap spacing and flow structure mechanism around cylinders: single cylinder body regime, reattachment regime and co-shedding regime. The results also show that in a particular regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The overall agreement of current and previous results indicates that the current code calculated the results efficiently. Furthermore, we refer readers for the details of quantitative as well as qualitative validation in the case of flow around two and more inline arranged cylinders to Abbasi et al (2018) and Abbasi et al (2020). It may therefore be concluded that our code is well established and that we can use it for flow around tandem arranged cylinders, done in the present study.…”
Section: Code Validationmentioning
confidence: 58%
“…The overall agreement of current and previous results indicates that the current code calculated the results efficiently. Furthermore, we refer readers for the details of quantitative as well as qualitative validation in the case of flow around two and more inline arranged cylinders to Abbasi et al (2018) and Abbasi et al (2020). It may therefore be concluded that our code is well established and that we can use it for flow around tandem arranged cylinders, done in the present study.…”
Section: Code Validationmentioning
confidence: 58%